New cellular mechanisms of gap junction degradation and recycling. (6th May 2015) - Carette, Diane; Gilleron, Jérôme; Denizot, Jean‐Pierre; Grant, Kirsty; Pointis, Georges; Segretain, Dominique
Research article By using a combination of time‐lapse fluorescence microscopy and high‐resolution transmission electron microscopy, we evidenced new specific cellular events concerning gap junction degradation and recycling. We demonstrated, for the first time, that an entire annular gap junction can be fully recycled back to the plasma membrane. In addition to canonical autophagy and heterophagy pathways, we discovered that both pathways could sometimes intermingle. Our results also highlighted a new lysosome‐based autophagy pathway that could play a pivotal role in common autophagy degradation.